Strategies to enhance nurse educator–student interaction in the higher education classroom environment: A Limpopo Province study - Mathevula, Rirhandzu Friddah; Mathebula, Letta (Orapuh Journal, 2026)
Introduction The effectiveness of nurse education largely depends on meaningful engagement between nurse educators and student nurses in the classroom environment. Positive classroom interaction supports active learning, improves knowledge acquisition, and promotes the development of critical thinking abilities essential for professional nursing practice. Purpose The study aimed to explore strategies to enhance interaction between nurse educators and novice student nurses within the higher education classroom environment in Limpopo Province. Methods A qualitative descriptive design was employed. Three nurse educators were selected using purposive sampling, and data were collected through in-depth, face-to-face semi-structured interviews. A sample of 25 student nurses was selected using stratified random sampling and participated in focus group discussions. The group consisted of 10 males and 15 females. Data analysis was guided by Tesch’s method, a systematic eight-step qualitative data analysis process commonly used in nursing research to identify themes from textual interview data. Results The findings revealed three key factors influencing educator–student classroom interaction: the classroom environment, teaching methods, and educator attitudes. Students reported that overcrowded classrooms hindered concentration, questioning, and meaningful interaction. They preferred active and participatory approaches—such as case studies, group discussions, and problem-based learning—over traditional lectures. Educator approachability, respect, and the creation of a safe learning space were considered critical. One student noted that being listened to made them feel valued and encouraged positive interaction. Using Peplau’s Theory, the study identified building trust and safety, promoting collaborative knowledge exchange, and fostering independence and reflection as key strategies for enhancing educator–student classroom interaction. Conclusion A key recommendation is that nursing programmes should limit class sizes in foundational courses to a maximum of 40 students and implement structured training for educators in interactive, student-centred teaching approaches to improve classroom interaction and overall learning quality.